COVID-19 lockdown policy impact on students' psychological, behavioral, and daily routine changes: A case study of Gusau residents in Nigeria - OJETUNDE, Ayodeji Oluwatobi; BAMIGBALA, Olateju Alao; OYEGOKE, Toyese (Universitas Negeri Makassar, 2020)
In the exploration of a better approach to managing education sectors in developing nations during the pandemic era, this study attempts to evaluate the impact of the COVID-19 lockdown policy on students' mental health in Gusau, one of the towns in Nigeria, through the investigation of how the students' psychology, behavior, and routine activities were affected by the introduction of lockdown protocols/policy during the COVID-19 pandemic crisis. The investigation was done using a hybrid method that employs a combination of the descriptive and factorial design method, where 201 students participated in the study. Findings from the study indicated that male students were 2% above female; two-third of the students were under-age; the students' attending private schools were 5% above the ones attending public schools; while two-third of the students were attending lower/middle school. The study confirmed that the students' psychology was significantly affected by the lockdown protocols, likewise their behaviors and routine activities. Some factors contributing to the effects were reported. And recommendations were made to the effect for the government to transform Nigeria states' learning system into being a hybrid learning system that would combine the use of both physical and virtual learning platforms at all levels of education, which would go a long way to manage the behavior, psychology, and routine activities of the students better, both during a pandemic and non-pandemic era